Evolution of the content of competitive programs of qualified athletes in acrobatic rock and roll - Nataliya Batieieva; Petro Kyzim; Artem Hryshko (Kharkiv State Academy of Physical Culture, 2024)
Background and Study: The modern type of competitive activity of qualified athletes of acrobatic rock and roll is undergoing contradictory changes in the content of the competitive program "Acrobatics" of the category "Main class contact style" due to an increase in the static performance of acrobatic elements, their number in combinations, where a loss of dynamics in the implementation of the competitive program is observed, which contradicts the definition of "rock and roll" as a dance where the acrobatic elements performed are the emotional, culminating accents of the dance figures. The main purpose of the study is to identify the patterns of the evolutionary process of the content of competitive programs of qualified acrobatic rock and roll athletes. Material and methods. As a result of the study, a comparative analysis of video materials of the final part of the competition was carried out: the final of the Ukrainian Championship in the category "Basic class contact style" (2010) 6 pairs (n=12); final of the Ukrainian Championship in the category "Basic Contact Style Class" (2023) - 6 pairs (n=12); final of the World Championship category "Basic freestyle class" (2011) -7 pairs (n=14); final of the World Championship category "Basic freestyle class" (2020) - 7 pairs (n=14). Results. During the analysis of viewing video materials of the final part of the Ukrainian and World Championships, structural changes were identified that affected the percentage of components of the competitive program "Acrobatics" in the category "Basic class contact style", where acrobatic elements and their combinations with a large number of their components become a priority in the competitive program in relation to the structure of the competitive program "Acrobatics" of the category "Main class free style". Conclusions. The evolutionary process of the content of the competitive program in acrobatic rock and roll has been identified, which is carried out due to changes in the Competition Rules, the implementation of new achievements of choreographic different styles of dance figures and the search for extreme, optimally adjusted motor actions in performing complex (high-risk) actions, which in the future involves changes and differentiation of the components of the educational and training process of qualified acrobatic rock and roll athletes.